Design and field testing of a rover with an actively articulated suspension system in a Mars analog terrain. Issue 7 (9th September 2018) - Cordes, Florian; Kirchner, Frank; Babu, Ajish
Abstract: This study presents the electromechanical design, the control approach, and the results of a field test campaign with the hybrid wheeled‐leg rover SherpaTT. The rover ranges in the 150 kg class and features an actively articulated suspension system comprising four legs with actively driven and steered wheels at each leg's end. Five active degrees of freedom are present in each of the legs, resulting in 20 active degrees of freedom for the complete locomotion system. The control approach is based on force measurements at each wheel mounting point and roll–pitch measurements of the rover's main body, allowing active adaption to sloping terrain, active shifting of the center of gravity within the rover's support polygon, active roll–pitch influencing, and body‐ground clearance control. Exteroceptive sensors such as camera or laser range finder are not required for ground adaption. A purely reactive approach is used, rendering a planning algorithm for stability control or force distribution unnecessary and thus simplifying the control efforts. The control approach was tested within a 4‐week field deployment in the desert of Utah. The results presented in this paper substantiate the feasibility of the chosen approach: The main power requirement for locomotion is from the drive system, active adaption only plays a minor role in power consumption. Active force distribution between the wheels is successful in different footprints and terrain types and is not influenced by controlling the body's roll–pitch angle in parallel to the force control. Slope‐climbing capabilities of the system were successfully tested in slopes of up to 28° inclination, covered with loose soil and duricrust. The main contribution of this study is the experimental validation of the actively articulated suspension of SherpaTT in conjunction with a reactive control approach. Consequently, hardware and software design as well as experimentation are part of this study.